Epidermal Growth Factor Receptor Mutation Status and Response to Tyrosine Kinase Inhibitors in Advanced Chinese Female Lung Squamous Cell Carcinoma: A Retrospective Study - Chang, Qing; Qiang, Huiping; Qian, Jialin; Lei, Yuqiong; Lu, Jiahuan; Feng, Hui; Zhao, Yiming; Han, Baohui; Zhang, Yanwei; Chu, Tianqing (Frontiers in Oncology, 2021)
Background The frequency of epidermal growth factor receptor (EGFR) mutations and the efficacy of tyrosine kinase inhibitor (TKI) in Chinese female patients with lung squamous cell carcinoma (SCC) are unknown. This study was designed to investigate the incidence of EGFR mutations and the role of targeted therapy in advanced Chinese female lung SCC patients. Methods Advanced female patients diagnosed with lung SCC at the Shanghai Chest Hospital between January 2013 and December 2018 were retrospectively analyzed. Results A total of 4223 advanced lung SCC patients were screened, and there were 154 female lung SCC patients who had underwent EGFR mutation detection. Positive EGFR mutations were found in 29.9% (46/154) of female lung SCC patients, including twenty-three 19del mutation (14.9%), twenty-one 21L858R mutation (13.6%) and other mutations (1.4%, 21861Q and 20ins). For 45 EGFR positive mutation female SCC patients, the median progression-free survival (PFS) of patients who received EGFR-TKI therapy (n=38) was 8.0 months (95% CI, 5.4-10.7 months), which was significantly longer than patients who were treated with chemotherapy (8.0 vs. 3.2 months, p=0.024), and the median overall survival (OS) was also longer (24.9 months vs. 13.9 months, p=0.020). The objective response rate (ORR) was 44.7% (17/38), and the disease control rate (DCR) was 81.6% (31/38). For 105 female SCC patients with EGFR negative mutation, the median OS was 18.6 months (95% CI, 14.2-22.9 months) and it was no different from that of EGFR positive mutation patients (18.6 vs. 22.8 months, p=0.377). Conclusion For advanced Chinese female lung SCC patients with EGFR positive mutations, targeted therapy could confer longer PFS and OS than chemotherapy, but the survival was similar with patients who were negative EGFR mutations.